Prophetic Wisdom: Engaged Buddhism's Struggle for Social Justice and Complete Liberation - Strain, Charles R. (SUNY Series in Religious Studies, 2024)
Shows how Engaged Buddhists can expand their understanding of the causes of collective suffering and develop nonviolent means for social transformation through a dialectic of love, power, and justice.